Dimensionamento do projeto mecânico do acionamento de um skate longboard voltado para mobilidade urbana - Mattheus, Torquato (2017)
The topic of this final paper is mechanical designing for the automation of a longboard skate and it is based on the reality of brazilian urban mobility. The need to develope new means of transportation is because the public ones are inefficient, concerning the needs of the user, and the urban environment is completely flooded with private vehicles in consequence of the previous cause. It is necessary to think about future technologies to satisfy the wishes and desires of the society which today is young and in a couple of years will be determining the future of public policy. The current generation, classified by many scholars as Z generation, and the next one, defended by Mark McCrindle as alpha generation, are the ones that were born connected and have a different perspective of the world. Subjects like sustentability, connectivity, the intense and trasient relationships, determine these generations. To develope a project that satisfy the needs of the society, and in the same way helps to change it, is very challenging. The challenge is multidisciplinary with a lot of steps, therefore this paper will concern only about the mechanical study envolved on the development of the automation of a longboard skate to the urban mobility. So, initially the paper brings the subjective aspects of the project, contextualizing the topic and its objectives. Then, the theoretical validity is composed with the subjects: skate, urban mobility and mechanical design. After knowing the context that the product is inserted, the stages of the development of the mechanical system can be listed accordingly to the objectives established for this paper. The theorical fundaments are based on, the powertrain, motor explaining briefly how a BLDC motor works and comparing it with brushed motors and with induction motors, and power transmission giving the general idea of the possibilities of using certain types of transmission (different types of belts or CVT) for the project. Then it is described the brazilian urban mobility, to situate the purpose of use of the product designed. And to end these fundaments, it is written about the use of an adaptation of a design metodology. After the theorical fundaments, the development takes it place and the first step is to analyze the project requeriments from the benchmarking, followed by the selection of the solutions and requeriments of the entries to evaluation, the powertrain design of the proposed system, the assembly steps, and the list of components used to make the mechanical system.